Rzymskie importy ceramiczne z cmentarzyska w Zadowicach pod Kaliszem - Kaszewska, Eleonora (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The cemetery at Zadowice is the biggest site of the Przeworsk culture in Great and in Central Poland to have been fully explored. The earliest burials date to Hallstatt D and the latest to the early 5th century A.D. The cemetery was excavated in 1944 and for 21 seasons following World War II. The discoveries include about 900 cremation burials, several symbolic graves and features of earlier and later date than the cemetery itself. Among Roman imports, clay artifacts, notably terra sigillata, form a fairly numerous group. About 100 mostly small terra sigillata sherds have been found, of which only a dozen or so come from 5 graves while the others are stray finds. The terra sigillate finds of 1944 represent 5 vessels (pi. II; 1-5). The largest fragments bear ornament similar to that occurring on pottery from Januarius II’s workshop at Rheinzabern, and grave 9 (pi.II; 10-13) yielded terra sigillata produced in Helenius’ workshop at Westerndorf. Yet another potsherd can be assigned to the Rheinzabern centre (pi. II; 7). Among other fragments upper parts of 7 vessels have been discerned (pi. I; 8 11, 13, 15; II; 8). The vessel from grave 281 (pi. I; 17) is a Pannonian import. On the other hand, the provenance of small vessels (pi. I; 1, 2) and of those ornamented with a wavy line (pi. I; 4-7) is not known. However, for lack of paralles in the Przeworsk pottery they, too, can be regarded as imports. A clay scarab (pi. I; 3) found in grave l)5 is part of the grave furniture of a rich woman, the owner of melon-shaped beads and other silver and gold ornaments melted during cremation. The provenance of the scarab has not yet been established. The cemetery was located on an important trade route and this location is reflected in the grave goods which include various imports, some of them unique, i.e. the vessel from grave 281, the scarab and the wheel-made pottery.